Phase-field modelling of brittle fracture with Smoothed Radial Point Interpolation Methods. (May 2022) - Novelli, Larissa; Gori, Lapo; da Silva Pitangueira, Roque Luiz
Abstract: The phase-field modelling of brittle fracture is an efficient tool for the modelling of complex cracks, since it is capable to predict crack initiation and branching, as well as the merging of cracks. While there are a number of papers in the literature devoted to the application of different meshfree methods to the phase-field modelling of fracture, this paper is, to the authors knowledge, the first application of the methods of the Smoothed Point Interpolation Methods (SPIM) family. The smoothing operation, that is used to approximate the displacements gradient in standard SPIM strategies, is here extended to the additional variable of a phase-field model. A number of numerical simulations, performed considering different kind of smoothing domains and support nodes selection strategies, illustrates the characteristics of the proposed approach. Highlights: The applicability of Smoothed Point Interpolation Methods to phase-field modelling of fracture is discussed. The weakened-weak form concept is extended to the phase-field modelling of fracture. The behaviour of different kinds of smoothing domains and support nodes selection strategies is investigated.